Dietary studies of three college girls - Cowles, Bertha (My University, 1905)
Introduction: During the last ten or fifteen years great progress has been made in all lines of scientific investigation. Especially has this true regarding the science of the nutrition of the body, both animal and human. Great strides have been made in this, but even now very little can be said to be positively known regarding the requirements of that body. It is known that the tissues of the body consist of carbohydrates, proteids, fats and minerals, and that certain amounts of these materials must be taken into the body at intervals to replace what is lost in the activities of life. From this food, is evolved by means of complicated processes called metabolism, the energy necessary to life. This energy is shown not only in work, but also in body heat and nervous force. This energy is measured in heat units, which are calories, because heat may be transformed into other kinds of energy. The heat or energy which each food is capable of yielding to the body and the approximate amount that will be needed for a day have been calculated. Further, the relative amounts of the energy to be provided by the different food principles have been determined. The heat of the various foods is, of course, found by chemical means. One method used in determining these requirements, is to make what are called dietary studies of individuals or groups of individuals for stated lengths of time. Notes are kept as to the actual amounts of the different foods eaten (sometimes also its cost). Then, either by means of direct analysis of the specimens of the foods or by means L' tables of averages of analyses, the amounts of the various nutrients fats, proteids, carbohydrates - taken into the body, can be determine together with the energy which they are capable of yielding. From this also can be calculated the ratio of the energy yielded by proteids to hat yielded by the other nutrients.
Citation: Cowles, Bertha. Dietary studies of three college girls. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Carbohydrates; Proteids; Fats; Minerals; Theses